Pedagogy and didactics: outline of differences, tensions, and relations of two fields (2016)
Pedagogy and Didactics are two fields whose nature, means, and aims reflect the contemporary debate of education. Education aims to see the movement of freedom in nature, since it is self-determination. Daughter of modern thought, Pedagogy seeks to understand the goals of education. Product of a society of control, Didactics sets its limits in learning. These two concepts reveal -because of their nature- tensions, differences, and relationships. In this paper some notions about the configuration of these concepts are outlined and some ideas on the urgency of the contemporary debate are placed.